Tekanan Darah Penumpang Laki-Laki yang Terpapar Suara Mesin Kapal Klotok Jalur Pontianak Teluk Batang - Ari Hepi Yanti, Erlita Hariani, Tri Rima Setyawati, (Universitas Tanjungpura, 2014)
Klotok ship is one of transportation that was used in West Kalimantan. The engine sound from the ship has negative impact on passengers health. The purpose of this research is to find out correlation between noise in klotok ship and blood pressure of male passengers. The research used interview with 90 respondents noise measure in ship and blood pressure passengers. The research analysed age of passengers, frequency of using the ship, smoking habits, hipertension, and types of jobs. The current research used regression analysis to measure intensity of the engine sound of ship and blood preassure. The approximate intensity of engine sound was 93,49 dBA. The intensity of engine sound was the main factor of blood prassure passenger increase. Based on the analysis of Y= 152,20+0,001X and Y=94,73+0.0001X, it showed that there was significant correlation between engine sound of klotok ship systolic and diastolic blood pressure of male passengers.